2019
DOI: 10.3389/fmicb.2019.01466
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Perillaldehyde on Prophylaxis and Treatment of Vaginal Candidiasis in a Murine Model

Abstract: Vulvovaginal candidiasis is a common fungal infection afflicting women which is primarily caused by the yeast Candida albicans ( C. albicans ). It is imperative to introduce new drug classes to counter this threat due to the continuous emergence of drug-resistant cases in recent years. The purpose of this study was to clarify the in vivo antifungal activity of perillaldehyde (PAE) against C. albicans and to prove that P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
24
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 46 publications
3
24
0
Order By: Relevance
“…Neutrophils play a crucial role in the inflammatory response during the corneal antifungal immune response, whereas excessive neutrophil infiltration often results in severe damage to corneal tissue, which is detrimental to fungal clearance. 39 41 A previous study in the mouse model of Candida albicans ( C. albicans ) vaginitis have confirmed that as the PAE concentration increased, the neutrophil counts in the mouse vaginal tissue decreased significantly, and the tissue integrity was gradually restored 42 ; Uemura reported that PAE can reduce the infiltration of inflammatory cells in colitis intestinal epithelial tissue, 17 suggesting that PAE can exert anti-inflammatory effects by inhibiting neutrophils recruitment to the corneal stroma in FK.…”
Section: Discussionmentioning
confidence: 90%
“…Neutrophils play a crucial role in the inflammatory response during the corneal antifungal immune response, whereas excessive neutrophil infiltration often results in severe damage to corneal tissue, which is detrimental to fungal clearance. 39 41 A previous study in the mouse model of Candida albicans ( C. albicans ) vaginitis have confirmed that as the PAE concentration increased, the neutrophil counts in the mouse vaginal tissue decreased significantly, and the tissue integrity was gradually restored 42 ; Uemura reported that PAE can reduce the infiltration of inflammatory cells in colitis intestinal epithelial tissue, 17 suggesting that PAE can exert anti-inflammatory effects by inhibiting neutrophils recruitment to the corneal stroma in FK.…”
Section: Discussionmentioning
confidence: 90%
“…PAE seems to be a very attractive antifungal agent used for food storage. For a very long time now, PAE has been generally regarded as a safe flavoring ingredient for foods [5], and it has some hygienic functions, such as hypolipidemic action [42], protection against inflammation [43,44], and assisting in curing depression [45]. Besides, in our previous study, PAE showed an effective antifungal activity against some food-borne fungi, such as A. falvus [10], A. niger [9], and Ceratocystis fimbriata [46], with a striking inhibition of food decay, and against Candida albicans, which protects humans from candidiasis infection [44,47].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, traditional antifungal drugs have continuously posed problems, which include the increasingly serious problem of drug resistance, the toxicity of the chemical antifungal compounds, drug interactions, and the high costs. Research into new antifungal agents needs to be carried out urgently because of the drug resistance and the toxicity of the compounds currently available (Sarkar et al, 2014;Qu et al, 2019). Consequently, increasing numbers of scientists are exploring novel natural products from medicinal plants such as Geraniol and Citral in an attempt to solve the question of fungal drug resistance and with consideration for the natural low toxicity and high antifungal activity of these products (Atanasov et al, 2015;Tang et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Some scholars have suggested that phenolics can damage mitochondrial function through targeting antioxidative signal transduction and thereby inhibit pathogenic Aspergillus (Kim et al, 2004(Kim et al, , 2006. Our own previous studies have indicated that apoptosis-promoting compounds are a promising direction in the exploration for a novel antimicrobial drug, and many antifungal agents have been investigated through the apoptotic pathway, such as amphotericin B and anacardic acid (Tian et al, 2017;Qu et al, 2019). In addition, our recent research has shown that Nerol possesses an anti-A.…”
Section: Introductionmentioning
confidence: 99%